PRECISE 40AR-39AR AGES FROM THE METAMORPHIC SOLE ROCKS OF THE TAURIDE BELT OPHIOLITES, SOUTHERN TURKEY: IMPLICATIONS FOR THE RAPID COOLING HISTORY - Çelik Ö.F.; Delaloye M.; Feraud G. (My University, 2006)
The Tauride Belt Ophiolites in southern Turkey are located on both sides of the E-W-trending, Mesozoic Tauride carbonate platform. They comprise the Lycian, Antalya, Beyşehir, Mersin, Alihoca and Pozanti-Karsanti ophiolites from west to east. Each ophiolite has a metamorphic rock unit either at the base of the peridotites or in the mélange units. The metamorphic sole rocks generally consist of amphibolite at the top and near the contact with the overlying tectonized harzburgite of the ophiolites, and mica schists mostly at the base, near the tectonic contact with the underlying ophiolitic mélange. 40Ar-39Ar measurements from the metamorphic sole rocks of the Lycian, Antalya and Beyşehir ophiolites are the first precise ages dating intra-oceanic thrusting and the cooling age history during the closure of the Neotethyan Ocean. Amphiboles and white micas from the metamorphic sole rocks of the ophiolites yielded 40Ar-39Ar ages between 90.7 ± 0.5 Ma and 93.8 ± 1.7 Ma and between 91.2 ± 2.3 Ma and 93.6 ± 0.8 Ma, respectively. Hornblende plateau ages from the amphibolites of the Lycian ophiolites (near Köyceǧiz) agree with those of Antalya, indicating that they were metamorphosed simultaneously in the Neotethyan Ocean. The white micas display plateau ages concordant with the amphiboles from the same units in Köyceǧiz and Yeşilova (Lycian ophiolites) and from the Pozanti-Karsanti ophiolite, suggesting that the metamorphic sole rocks were rapidly cooled after their generation. © 2006 Cambridge University Press.
Keywords: EAST MEDITERRANEAN; GEOCHRONOLOGY; NEOTETHYS; OPHIOLITE; TURKEY